우리나라 로스쿨에서의 로여링 교육의 과제와 전망 - 최성수(Choi Sung-Soo) (Tonga pŏphak, 2011)
로스쿨제도에서 가장 중요한 부분은 교육과정이다. 로스쿨은 실무교육을 강조한다. 미국 로스쿨에서의 법교육은 현재 case method에서 임상법학적 방법의 강조로 그 중점이 변화하고 있다. 우리 나라 로스쿨에서의 실무교육도 실질적인 것이 되려면 임상법학적 방법을 널리 채용하여야 한다. 로여링은 그 일환이다. 이를 통하여 다양한 로여링 기술을 익힌다. 로여링교육의 중요성을 인식하고 우선 이 분야에 대한 관심을 높여야 한다. 로여링 교육의 내실화를 위해서 커리큘럼을 잘 구성하여야 하고, 학교에서 실제 사건을 취급해볼 수 있도록 학교내 법률사무소의 설치근거를 마련하는 것도 과제이다. 실제 진행되는 사건을 다루어 볼 수 있는 기회를 마련하는 학생실무모델규칙등의 제정도 필요하다. 준비된 교원의 양성도 필요하고 임상법학 교육에 들어가는 예산의 지원도 뒤따라야 할 실정이다. 로여링은 단순한 기술의 습득만을 위한 과정은 아니다. 기술과 함께 가치중심의 로여링도 함께 병행하여 소위 문무를 겸비한 변호사를 배출하는 것이 목표이다. 로스쿨 시대의 변호사는 이론교육, 실무교육, 윤리교육, 특성화 교육으로 무장된 경쟁력 있는 변호사를 지향한다. 그 시발점에 로여링, 리걸 클리닉 등 임상법학교육이 자리하고 있다. In the Law School system, the most important part is the curriculum. Law School system emphasizes a practical training. Legal education of Law School in the United States currently emphasis on the clinical method, so is changing its focus from case method to clinic method. If we want a practical training in our law school system to be substantial, clinical method should be adopted widely. Lawyering is part of that. Through this course, we can learn the various lawyering skills. Firstly we need to recognize the importance of lawyering education, and to increase interest in this field. For lawyering education to be profitable, we need to organize well the curriculum. To get an actual case in Law school, we need to install the legal background of in-house clinic. Also we need to establish a Model Student Practice Rule that let students to treat the actual case dealt with the real progress. Prepared teachers are also needed and a budget support for training and clinical legal education should be followed. Lawyering is not only for course getting technical mastery. With lawyering technology, so-called value-oriented lawyering is also pursed in this course, at the result of that, we can discharge a lawyer who are theoretically and practically prepared to the field. Law school-era lawyer orients a competitive lawyer armed with theoretical education, practical training, ethics training and specialized education. To its starting point, a clinic method including lawyering and legal clinics is situated. KCI Citation Count: 1